SURVEY OF TOURISTS' SATISFACTION LEVEL WITH POST COVID 19 TAMANI FAITH TOURISM OBJECTS YEAR 2023 - Manurung, Jenny S; ibrahim, ibrahim (Universitas Negeri Medan, 2023)
This research aims to obtain empirical facts about a survey of tourist satisfaction levels with the Taman Iman tourist attraction after Covid 19 in 2023. This type of research is descriptive research, namely research conducted on independent variables without making comparisons or connecting them with other variables. Descriptive research is not intended to test a particular hypothesis, but only describes